As a single atom Pd outperforms Pt as the most active co-catalyst for photocatalytic H2 evolution - Cha, Gihoon; Hwang, Imgon; Hejazi, Seyedsina; Dobrota, Ana S; Pašti, Igor A; Osuagwu, Benedict; Kim, Hyesung; Will, Johannes; Yokosawa, Tadahiro; Badura, Zdeněk; Kment, Štěpán; Mohajernia, Shiva; et al. (iScience, 2021)
Here, we evaluate three different noble metal co-catalysts (Pd, Pt, and Au) that are present as single atoms (SAs) on the classic benchmark photocatalyst, TiO2. To trap the single atoms on the surface, we introduced controlled surface vacancies (Ti3+-Ov) on anatase TiO2 nanosheets by a thermal reduction treatment. After anchoring identical loadings of single atoms of Pd, Pt, and Au, we measure the photocatalytic H2 generation rate and compare it to the classic nanoparticle co-catalysts on the nanosheets. While nanoparticles yield the well-established the hydrogen evolution reaction activity sequence (Pt > Pd > Au), for the single atom form, Pd radically outperforms Pt and Au. Based on density functional theory (DFT), we ascribe this unusual photocatalytic co-catalyst sequence to the nature of the charge localization on the noble metal SAs embedded in the TiO2 surface.
Keywords: Catalysis; Materials characterization; Nanomaterials